3D printed and structurally strengthened ammonia sensor. (December 2020) - Zhou, Shixiang; Mei, Hui; Lu, Mingyang; Cheng, Laifei
Abstract: To cater to the complex needs in gas monitoring under harsh conditions, highly reliable and highly customized gas sensors with excellent sensing performance are in demand. Body-centered periodical mullite based ammonia sensors were fabricated by 3D printing for highly reliable ammonia detection. The printed substrates were modified with Ag nanoparticles decorated PANI network. NH3 molecules can react with PANI to withdraw protons, leading to the localization of polarons and increasing the resistance. Additionally, the Ag nanoparticles provided more active sites for NH3 molecules adsorption, enhancing the sensing performance. The sensor exhibited a response value of 9.7–100 ppm NH3 and excellent selectivity at room temperature. More importantly, the sensors had an excellent mechanical performance with the compressive strength and energy absorption of 23.71 MPa and 243.09 kJ/m 3, respectively, ensuring stable operation under stress. The strategy may shed light on the production of reliable and tailor-made gas sensors.